Шляхи гармонізації ставок ПДВ з європейськими: проблеми та виклики - Гаркушенко, О.М.; Філіппова, Н.В. (Економіка промисловості, 2016)
Уточнено сутність поняття «гармонізація» з урахуванням існуючих досліджень та європейської практики. На основі аналізу європейського податкового законодавства та практики застосування ПДВ розроблено напрями гармонізації ПДВ в Україні: стандартної ставки ПДВ, знижених ставок ПДВ та ефективної ставки ПДВ. У результаті розрахунку коефіцієнта С-ефективності встановлено, що в Україні необхідно звузити податкову базу, за якою використовуються знижені ставки ПДВ, та вдосконалити адміністрування цього податку. Уточнена сущность понятия «гармонизация» с учетом существующих исследований и европейской практики. На основе анализа европейского налогового законодательства и практики применения НДС разработаны направления гармонизации НДС в Украине: стандартной ставки НДС, пониженных ставок НДС и эффективной ставки НДС. В результате расчета коэффициента С-эффективности установлено, что в Украине необходимо сузить налоговую базу, по которой используются пониженные ставки НДС, и усовершенствовать администрирование этого налога. Value added tax has proved itself as quite simple and effective fiscal instrument, implementation of which simplifies trade relations between member countries of international associations and helps to decrease the scope of tax frauds in international trade. However, increasing of its efficiency demands the harmonization of the tax by Member States and countries willing to enter such unions. But this task is complicated due to the fact that VAT harmonization within EU is not finished yet.In the case of VAT it is necessary to clearly distinguish what tax rate should be harmonized: standard, reduced or directions of VAT harmonization can be pointed out by calculation of an effective rate. In addition, as long as for now there is significant difference between legislation and practice in the EU the harmonization of VAT towards EU needs clarification in terms of how this process will take place: according to the legislative norms or the Member States practice. Considering the above, European VAT legislation and practical implementation of this tax in the EU have been analysed in the paper. On this basis the recommendations and proposals for the harmonization of the standard, reduced, and effective VAT rates in Ukraine have been developed.Also by calculating of C-effectiveness coefficient and comparing results of the calculation with the European ones we have found that in Ukraine there are problems with tax compliance, VAT administration and the usage of the broad tax base, to which reduced VAT rates are applied. These problems are also in need of a solution that can be a perspective direction for further researches.